A New Compound (8,9) -Furanyl-Pterocarpan-3-Ol Used for Standardization of Bengkuang (Pachyrhizus erosus) Extract as Sunscreen and Skin Whitening Agent - Endang Lukitaningsih; Ulrike Holzgrabe (ISCC (Indonesian Journal of Cancer Chemoprevention), 2019)
Bengkuang (Pachyrhizus erosus) has been traditionally used as sun screening and skin whitening. The active compounds in bengkuang extract already published included their activities in antioxidant and skin whitening. However, standardization of bengkuang extract has not been studied. This research aims to find out the analysis procedure by High Performance Liquid Chromatography to make standardization bengkuang extract.